Validation of a novel high-sensitivity cardiac troponin assay. (3rd October 2022) - Restan, I; Steiro, O T; Tjora, H L; Langoergen, J; Omland, T; Collinson, P; Bjoerneklett, R; Vikenes, K; Steinsvik, T; Skadberg, O; Mjelva, O R; Larsen, A I; et al.
Abstract: Background: The accuracy for early identification of non-ST-elevation myocardial infarction (NSTEMI) in the emergency department must be determined for all novel high-sensitivity cardiac troponin assays (hs-cTn). In this prospective, multi-centre study we developed rule-out algorithms for a high-sensitivity cardiac troponin I (hs-cTnI) assay and compared it to established algorithms for hs-cTnT and hs-cTnI. Methods: Two rule-out algorithms for NSTEMI were developed from a derivation cohort of 977 patients assessed by the Siemens Atellica IM hs-cTnI assay. Diagnostic performance was compared with hs-cTnT (Roche) and hs-cTnI (Abbott) algorithms. The derived algorithms were tested in two different validation cohorts (n=518 and n=405, respectively). Results: An admission sample algorithm (hs-cTnI (Siemens)) for rule-out of NSTEMI with cutoff <5 ng/L had negative predictive value (NPV) 99.4–100.0%, sensitivity 98.3–100% and specificity 46.7–56.5% in the two validation cohorts. Sensitivity and NPV was similar, specificity trended towards improvement over the comparator algorithms (Figure 1). A 0–1 hour algorithm (hs-cTnI (Siemens)) with cutoff <10 ng/L and Δ change <3 ng/L achieved sensitivity and NPV 100% with specificity >70% in both validation cohorts, similar to the comparator algorithms (Table 1). Conclusions: Rule-out algorithms from the Siemens Atellica hs-cTnI assay has comparable diagnostic accuracy to established hs-cTn rule-out algorithms. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Public grant: Western Norway Regional Health Authority.Private company funding: Siemens Healthineers AG